Caribbean Report 12-01-1990 - Fraser, Sonia (anchor); King, Bob (correspondent); Mathur, Ira (correspondent); Jones, James (interviewee); Wilson, Tracy (interviewee); DeJean, Rob (interviewee); Russell, Lynsey (correspondent); Fortescue, Edna (interviewee); Shatner, John (interviewee); Humphreys, Hilroy (interviewee); Dark, Ian (correspondent) (The British Broadcasting Corporation, 1990)
The program focuses on the strengthening of ties between Haiti and Taiwan through the recent visit of President Avril to Taipei, resulting in the Taiwanese offering advisory assistance to the development of the Haitian economy and trade. Secondly, trade unions in Trinidad condemn its Government’s retrenchments in the transportation sector and are encouraged to be less reliant on government subsidies. Following the Financial Market news, Antigua’s government faces a lawsuit by the American owners of the surviving llamas awaiting transportation to the US. The round-up segment addresses the return of prisoners to St. Croix after Hurricane Hugo; the call by a Birmingham City Counsellor, Phillip Murphy, to provide Jamaican dialect translation over a public address systems in city halls; and TV Marti in Cuba. The program concludes with Nigel Benn, Barbadian boxer vying for the World Middle Weight title against Sanderline Williams.
1. Headlines (00:00 - 00:36)
2. Hatian President Prosper Avril visits Taiwan. Bob King reports from Taipei (00:37-02:38)
3. Retrenchments in transportation services garner condemnation from trade unions in Trinidad and Tobago. Ira Mathur interviews James Jones, Vice President of Transport and Industrial Labour Union and Tracy Wilson, spokesman for PTSC (02:39-04:53)
4. Financial News. Interview with Rob DeJean on coffee prices (04:54-06:27)
Keywords: Haiti -- Foreign relations -- Taiwan.; Trade unions -- Trinidad and Tobago.; Llamas -- Protection -- Caribbean Area.; Llamas -- Antigua.; Boxing matches.; Benn, Nigel.; Williams, Sanderline.